Pre-exposure Prophylaxis: The Delivery Challenge - Venter, Willem D. F. (Frontiers in Public Health, 2018)
HIV pre-exposure prophylaxis (PrEP), despite its efficacy, has been slow in uptake everywhere inthroughout the world. This article discusses the operational and service delivery complexity, based on early real-world experience, with some recommendations on how this promising intervention could be made more available. Currently, access to PrEP is made complex by restricting delivery to dedicated health facilities, as well as requirements around HIV testing and toxicity monitoring. Expanding to verticalised services that focus on well-defined populations where HIV testing and treatment programmes already exist, has proven relatively simple. Providing PrEP outside of this environment has yet to be demonstrated at any scale, and will likely require innovative thinking addressing the regulatory and clinical environment, so as to ensure easier access to this promising HIV prevention tool.